Special Curves According to Extended Darboux Frame Field in ???? ?? - Erdem, Esra; Kulahci, Mihriban Alyamac; Yılmaz, Münevver Yıldırım (My University, 2021)
In this study, the involute of a curve is investigated in Minkowski space-time by using extended Darboux frame field and curves of the AW (k) type are studied in Minkowski space-time.
Keywords: Involute curve; Minkowski Space-Time; Extended Darboux Frame Field